Effect of microwave treatments on dimensional accuracy of maxillary acrylic resin denture base - Pavan, Sabrina [UNESP]; Arioli Filho, João Neudenir [UNESP]; Santos, Paulo Henrique dos [UNESP]; Mollo Jr., Francisco de Assis [UNESP] (FapUNIFESP (SciELO), 2005)
Microwave energy has been used as an alternative method for disinfection and sterilization of dental prostheses. This study evaluated the influence of microwave treatment on dimensional accuracy along the posterior palatal border of maxillary acrylic resin denture bases processed by water-bath curing. Thirty maxillary acrylic bases (3-mm-thick) were made on cast models with Clássico acrylic resin using routine technique. After polymerization and cooling, the sets were deflasked and the bases were stored in water for 30 days. Thereafter, the specimens were assigned to 3 groups (n=10), as follows: group I (control) was not submitted to any disinfection cycle; group II was submitted to microwave disinfection for 3 min at 500 W; and in group III microwaving was done for 10 min at 604 W. The acrylic bases were fixed on their respective casts with instant adhesive (Super Bonder®) and the base/cast sets were sectioned transversally in the posterior palatal zone. The existence of gaps between the casts and acrylic bases was assessed using a profile projector at 5 points. No statistically significant differences were observed between the control group and group II. However, group III differed statistically from the others (p<0.05). Treatment in microwave oven at 604 W for 10 min produced the greatest discrepancies in the adaptation of maxillary acrylic resin denture bases to the stone casts.
Keywords: Acrylic resin; Dimensional accuracy; Disinfection; Microwave oven; acrylic acid resin; adhesive agent; loctite; methacrylic acid derivative; polymer; chemistry; comparative study; dental care; denture; disinfection; human; materials testing; maxilla; methodology; microwave radiation; radiation exposure; surface property; time; Acrylic Resins; Adhesives; Dental Models; Denture Bases; Humans; Materials Testing; Maxilla; Methacrylates; Microwaves; Polymers; Surface Properties; Time Factors